2009
DOI: 10.1177/0011128709352234
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Differential Effects of Race and Ethnicity on Sentence Outcomes Under Different Sentencing Systems

Abstract: Although many states have adopted sentencing guidelines, questions remain about whether guidelines achieve one of their primary goals—reducing disparities that arise from such extralegal factors as race and ethnicity. To date, research has not taken a cross-state approach to testing for racial or ethnic disparity in sentences imposed in guideline and nonguideline states or to examining whether less disparity exists in states with voluntary or presumptive guidelines. To address this research gap and inform sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 51 publications
4
42
3
1
Order By: Relevance
“…Again, if this research had examined total incarceration time, as opposed to separating jail and prison, we would not have been able to conclude the potential bias against Black and White offenders (compared to Hispanic offenders) in terms of jail time and the apparent similarity in treatment with prison time. Therefore, although the jail length findings are not consistent with the limited prior research that separated the sentences, the prison length findings are consistent with those same studies (Freiburger & Hilinski, 2013;Wang et al, 2013).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Again, if this research had examined total incarceration time, as opposed to separating jail and prison, we would not have been able to conclude the potential bias against Black and White offenders (compared to Hispanic offenders) in terms of jail time and the apparent similarity in treatment with prison time. Therefore, although the jail length findings are not consistent with the limited prior research that separated the sentences, the prison length findings are consistent with those same studies (Freiburger & Hilinski, 2013;Wang et al, 2013).…”
Section: Discussioncontrasting
confidence: 70%
“…Although prior research found racial differences in the total incarceration variable (combined jail and prison; Feldmeyer & Ulmer, 2011;Spohn & Holleran, 2000;Steffensmeier et al, 1998), the research suggests that those findings may not hold when each sanction is examined separately (e.g., Freiburger & Hilinski, 2013;Harrington, 2008;Wang et al, 2013). We, however, found some racial influence when examining jail incarceration length, resulting in a bias against both Black and White offenders compared to Hispanic offenders.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…If race is playing a role in sentencing, one might expect that allowing for more discretion in departures would increase disparities. The data here are mixed, with one study of state courts showing greater racial disparities in states with less restrictive sentencing systems (Wang et al 2013). Studies of the federal system, however, show no such increase after the guidelines became less restrictive in 2005 (Fischman & Schanzenbach 2012).…”
Section: Foreign Litigantsmentioning
confidence: 67%
“…Even after controlling for demographic and legal characteristics, the observed racial disparities in criminal justice system and plea bargaining decision-making process are statistically significant [1,5]. Research [6,13,14] consistently documents that Blacks and Hispanics tend to be related to crime fear and are more likely to perceived as particularly threatening in the contemporary American community [13]. Specifically, argue that race is the most influential factor in the sentencing process and the court's offer of plea bargaining [15].…”
Section: The Role Of Legal Characters In Plea Bargainingmentioning
confidence: 98%